Fecal carriage of ESBL-producing E. coli and genetic characterization in rural children and livestock in the Somali region, Ethiopia: a one health approach - Abdifatah Muhummed; Ashenafi Alemu; Salome Hosch; Yahya Osman; Rea Tschopp; Simon Yersin; Tobias Schindler; Jan Hattendorf; Jakob Zinsstag; Guéladio Cissé; Pascale Vonaesch (Antimicrobial Resistance and Infection Control)
Abstract Background The emergence and spread of Extended-Spectrum Beta-Lactamase (ESBL)-producing Escherichia coli pose significant challenges for treatment of infections globally. This challenge is exacerbated in sub-Saharan African countries, where the prevalence of ESBL-producing E. coli is high. This, combined with the lack of a strong and supportive healthcare system, leads to increased morbidity and mortality due to treatment failures. Notably, studies in Ethiopia have primarily focused on hospital settings, leaving a gap in understanding ESBL prevalence in rural communities, where human-animal proximity may facilitate microbial exchange. Methods We conducted a community-based study in the rural Somali region of Ethiopia, simultaneously examining the fecal carriage of ESBL-producing E. coli in children aged 2–5 years and their livestock (cattle, camel, goat). Fecal samples from 366 children and 243 animals underwent phenotypic screening for ESBL-producing E. coli. Following phenotypic confirmation, ESBL resistance genes were identified via conventional PCR. Whole-genome sequencing (WGS) was performed on a subset of isolates from human feces. Results We found that 43% (159/366) of children and 3.7% (9/244) of livestock harbored ESBL-producing E. coli. The ESBL gene bla CTX-M-15 was predominant in human (82.7%, 120/145) and livestock (100%) isolates. In the 48 human E. coli isolates subjected to WGS, a high diversity resulting in 40 sequence types (STs) was observed. Among these, ST-2353 was the most prevalent (5/48), followed by ST-10 and ST-48 (3/48) and ST-38, ST-450, and ST-4750 (2/48). These STs were associated with multiple resistance genes, such as bla CTX-M-15, bla TEM-1B, bla OXA-1, bla CTX-M-14 and bla TEM-35. Conclusion We report a high prevalence of ESBL E. coli in rural children, which outnumbers its prevalence in livestock. These isolates displayed a high diversity of sequence types (STs) with ST-2353 being the dominant ST. Our study is the first to report the association of ST-2353 with multi-drug resistance genes in Ethiopia. Further research using an integrated approach including other domains such as water and food products is needed to truly understand and combat AMR transmission and acquisition in this region.